The extract of Boesenbergia rotunda attenuates neuronal loss and the activation of astrocytes within the hippocampus of rats following ischemic stroke. - Kongsui, Ratchaniporn; Sriraksa, Napatr; Thongrong, Sitthisak; Surapinit, Serm (Health Science, Science and Technology Reviews, 2019)
Ischemic stroke significantly provoked the induction of brain damage, in which all components are affected including neurons, glial cells and the vasculature. Nowadays, the preventive strategy of ischemic stroke, one of the most challenge problems in adult, especially in the elderly, has received highly attention due to the limitation of therapeutic efficacy. In this study, we aimed to investigate the protective effect of Boesenbergia rotunda extract on neuronal cell and the alterations of astrocytes in animal model of ischemic stroke. Adult male Wistar rats were orally given B. rotunda extract at dose of 200 mg/kg body weight at a period of 14 days before and 7 days after middle cerebral artery occlusion (MCAO). We found that stroke rats subjected to B. rotunda extract showed a significant increase of neuronal density in CA1 of hippocampus. In addition, decreased expression of glial fibrillary acidic protein (GFAP) was significantly observed in CA1 in stroke plus B. rotunda group. The results indicated that B. rotunda extract at dose of 200 mg/kg could suppress the neuronal loss associated with lower activation of astrocytes. Therefore, B. rotunda is the potential medicinal plant might prevent brain damage. However, further researches are essential to elucidate the possible active ingredient.